Perfil dietético antioxidante de mulheres climatéricas hipertensas do Sul do Brasil - Duarte, Priscila Boff (My University, 2021)
Introduction: Oxidative stress is involved in the pathophysiology of systemic arterial hypertension (HAS) and the role of antioxidants in this context still needs to be better understood. Objective: To evaluate the prevalence of hypertension and the relationship with polyphenol intake and total dietary antioxidant capacity (DTAC) in climacteric women from Serra Gaúcha, RS, Brazil. Materials and methods: Participants (n = 41) were subjected to measurements of weight, height, waist circumference, and blood pressure. Different questionnaires were applied to obtain sociodemographic and health information, in addition to the 24- hour Food Recall. Comparisons between the hypertensive and non-hypertensive groups were made using Student's t-test or chi-square. Results: The prevalence of HAS in the population was 30% and hypertensive women had a BMI statistically higher than non-hypertensive women (p=0.047). Although without a statistical difference, it was observed that the hypertensive group had decreased DTAC and total polyphenol intake (9 and 11% reduction, respectively). The mineral magnesium had its intake significantly reduced (30%; p=0.006) by hypertensive women. This group also had an intake below the recommended for vitamins A and E. Among the foods and beverages that contributed to increasing the participants' DTAC, coffee ranked first in both groups. Conclusion: These data demonstrate the importance of monitoring the consumption of antioxidants to prevent and/or control hypertension and diseases related to heart health in climacteric women. [resumo fornecido pelo autor]
Introdução: O estresse oxidativo está envolvido na fisiopatologia da hipertensão arterial sistêmica (HAS) e o papel dos antioxidantes nesse contexto ainda precisa ser melhor compreendido. Objetivo: avaliar a prevalência de hipertensão e a relação com ingestão de polifenóis e capacidade antioxidante total dietética (DTAC) em mulheres climatéricas da Serra Gaúcha, RS, Brasil. Materiais e métodos: As participantes (n=41) foram submetidas a aferições de peso, altura, circunferência da cintura e pressão arterial. Aplicaram-se diferentes questionários visando a obtenção de informações sociodemográficas e de saúde, além do Recordatório Alimentar de 24 horas. Comparações entre os grupos hipertenso e não hipertenso foram feitas através de teste t de Student ou qui-quadrado. Resultados: A prevalência de HAS na população foi de 30 % e as mulheres hipertensas apresentaram IMC estatisticamente superior ao das não hipertensas (p=0,047). Embora sem diferença estatística, observou-se que o grupo hipertenso apresentou DTAC e ingestão de polifenóis totais diminuídos (9 e 11 % de redução, respectivamente). O mineral magnésio teve sua ingestão significativamente reduzida (30 %; p=0,006) pelas mulheres hipertensas. Observou-se que as mesmas exibiram uma ingestão abaixo do recomendado para as vitaminas A e E. Dentre os alimentos e bebidas que contribuíram para aumentar a DTAC das participantes, o café ficou em primeiro lugar em ambos os grupos. Conclusão: Esses dados demonstram a importância do monitoramento do consumo de antioxidantes visando a prevenção e/ou controle da hipertensão e de doenças relacionadas à saúde do coração, em mulheres climatéricas. [resumo fornecido pelo autor]
Keywords: Nutrição; Climatério; Mulheres; Sistema cardiovascular - Doenças; Estresse oxidativo; Polifenóis; Vitaminas